Measuring the Impact of Digital Technology Adoption on the Operational Efficiency of MSMEs in Indonesia - Saleh, Citra; Mohamad, Santi; Talipi, Nuzlan; Budiawan, Shella (Amsir Accounting & Finance Journal, 2025)
This study aims to analyze the level of adoption of digital technology by MSMEs in Gorontalo and its impact on operational efficiency. Data was obtained through questionnaires and interviews involving MSMEs in various sectors, such as food and beverages, handicrafts, and services. The study results show that adopting digital technology includes using QRIS as a payment method, digital financial management applications such as SI APIK, and digital marketing through social media. The adoption of this technology has proven to have a positive impact on MSME operational efficiency, including reducing operational costs, increasing time efficiency, and improving the quality of service to customers. A simple linear regression analysis revealed a significant influence between the adoption rate of digital technology and the operational efficiency of MSMEs, with a p < p-value of 0.05 and a positive coefficient. The discussion showed that QRIS speeds up transactions and reduces the risk of losing cash, financial management applications increase accuracy and efficiency in financial management, and digital marketing increases the competitiveness of MSMEs. However, implementation costs and lack of digital literacy are still obstacles. These findings support previous research on the benefits and challenges of digitalization for MSMEs.